Genetically Engineered Erwinia carotovora in Aquatic Microcosms: Survival and Effects on Functional Groups of Indigenous Bacteria - Scanferlato, Vjera S. (1989)
The survival of genetically engineered Erwinia carotovora L-864, with a kanamycin resistance gene inserted in its chromosome, was monitored in the water and sediment of aquatic microcosms. The density of genetically engineered and wild-type E. carotovora strains declined at the same rate, falling in 32 days below the level of detection by viable counts. We examined the impact of the addition of genetically engineered and wild-type strains on indigenous bacteria belonging to specific functional groups important in nutrient cycling. For up to 16 days, the densities of total and proteolytic bacteria were significantly higher (P < 0.05) in microcosms inoculated with genetically engineered or wild-type E. carotovora, but by 32 days after inoculation, they had decreased to densities similar to those in control microcosms. Inoculation of genetically engineered or wild-type E. carotovora had no apparent effect on the density of amylolytic and pectolytic bacteria in water and sediment. Genetically engineered and wild-type E. carotovora did not have significantly different effects on the densities of specific functional groups of indigenous bacteria (P > 0.05).